Al-Kashshaf : Al-Zamakhshari's Mu'tazilite exegesis of the Qur'an - Ullah, Kifayat (Berlin : De Gruyter, 2017)
c
Chapter 8. Fifth Principle: Enjoining what is Right and Forbidding what is Wrong (al-amr bi al-ma°råuf wa al-nahy 'an al-munkar)Conclusion; Appendix: Al-Zamakhsharåi's Scholarly Contribution; Bibliography; Index of Names; Index of Subjects; Index of Qur®åan Citations
Description based upon print version of record.
Includes bibliographical references and index.
Master record variable field(s) change: 050, 072, 082, 600, 630
Keywords: Zamakhsharåi, Maòhmåud ibn °Umar, -- 1075-1144.; Qur®an -- Commentaries -- History and criticism; Zamaùhésaråi, Maòhmåud Ibn-°Umar Ĉaz-ĉ -- 1075-1144; Zamaùhésaråi, Maòhmåud Ibn-°Umar Ĉaz-ĉ -- 1075-1144; Mutasiliten; Islamische Theologie; Tafsir; RELIGION / Islam / General; Electronic books